Implementasi Perencanaan Kurikulum Sesuai Dengan Perkembangan Zaman (Studi Kasus di Madrasah Aliyah Negeri 3 Aceh Utara) - Wahyuni, Suci (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
This research aims to find out how the implementation of curriculum planning, whether it is in accordance with the development of the times applied in Madrasah Aliah Negeri 3 North Aceh and what are the factors that hinder the curriculum planning. This research is a field study with a descriptive qualitative approach. Data sources consist of primary data and secondary data. The data collection technique uses observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data and drawing conclusions from the data that has been collected. Meanwhile, to ensure the validity of the data, triangulation techniques with theory are used. The results of this study show that: (1) The planning of the MAN 3 North Aceh curriculum has been running in a structured manner such as the preparation of prota, prosem, time allocation program, syllabus, lesson plan, KKM and others, but it is still necessary to align the plans that have been made so that everything can be carried out as planned at the planning meeting which is held routinely at the beginning of the school year. (2) Obstacles that arise in the curriculum planning process at MAN 3 North Aceh are caused by human resources (HR) in madrasas. Lack of awareness of each individual's responsibility, cognitive ability, and professionalism of human resources are the main factors in the emergence of these obstacles. (3) As an effort to overcome the obstacles that arise, improving the quality of human resources is the main solution in the success of madrasah curriculum planning activities. Good madrasah resources will result in the achievement of educational goals optimally.